HIGH EXPERIENCE, LIMITED INFRASTRUCTURE: TOURIST EXPERIENCE IN A SMALL-ISLAND RELIGIOUS HERITAGE DESTINATION (MANSINAM ISLAND, INDONESIA) - Yansen M.I. Saragih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines how tourist experiences reflect the heritage value of Mansinam Island, a small-island religious heritage destination in Papua Barat, Indonesia. Despite the growing literature on heritage tourism and tourist experience, limited attention has been given to small-island contexts characterized by strong symbolic value but constrained infrastructure. Addressing this gap, this research adopts a qualitative-dominant mixed-methods approach to explore how experiential value is constructed in such settings. Data were collected from 40 international cruise tourists through structured questionnaires and short semi-structured interviews. The reliability of the instrument was confirmed using Cronbach’s Alpha (α > 0.70), while content validity was ensured through expert review. The data were analyzed using descriptive statistics and thematic analysis to capture both measurable patterns and deeper experiential meanings. The findings reveal that tourist experience in Mansinam Island is shaped by a dual structure consisting of nature-based experience (45%) and socio-cultural dimensions (40%), including cultural interaction, emotional responses, and engagement with local communities. The results also show consistently high levels of satisfaction, indicating the presence of memorable tourism experiences. However, a significant gap exists between experiential quality and infrastructural readiness, particularly in basic facilities and interpretive services. This study proposes the concept of a “high-experience, limited-infrastructure destination” to explain how destinations with limited physical development can still generate strong experiential value through social interaction and cultural meaning-making. The findings contribute to the advancement of religious heritage tourism literature and highlight the importance of community-based experiential development in small-island tourism contexts.